2022
DOI: 10.2478/atd-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mindfulness-Based Thriving Programs on High School Students’ Perceived Stress, Mindfulness, Thriving and Self-Efficacy Levels

Abstract: Introduction: Adolescence is a period of rapid change marked by increased stress levels. Individuals with high self-efficacy better alleviate the effects of the stress of this period by exerting conscious control over their own thoughts, behaviours and feelings – a trait strongly associated with mindfulness. In this regard, the concept of mindfulness-based self-efficacy has been a much-researched area in recent students. Mindfulness practices ensure individuals with vitality and energy since they learn to beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Studies in the literature also reported similar results supporting our finding and revealed that the MBSR program caused a significant increase in the selfefficacy levels of the participants. 30,31 Based on the literature, it can be argued that the MBSR program is a simple and cost-effective program that increases the self-efficacy levels of older adults.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the literature also reported similar results supporting our finding and revealed that the MBSR program caused a significant increase in the selfefficacy levels of the participants. 30,31 Based on the literature, it can be argued that the MBSR program is a simple and cost-effective program that increases the self-efficacy levels of older adults.…”
Section: Resultsmentioning
confidence: 99%
“…It enables students to access course materials, engage in virtual discussions, and submit assignments without the constraints of physical classrooms. Online course delivery is known for its flexibility and accessibility, accommodating diverse learning styles and catering to a broader student population [27], [28].…”
Section: Online Course Deliverymentioning
confidence: 99%